Synthesis, structures, photophysical properties, and catalytic characteristics of 2, 9‐dimesityl‐1, 10‐phenanthroline (dmesp) transition metal complexes. Issue 8 (17th February 2020) - Cetin, M. Mustafa; Shafiei‐Haghighi, Sara; Chen, Jiazhen; Zhang, Sheng; Miller, Amanda C.; Unruh, Daniel K.; Casadonte, Dominick J.; Lohr, Tracy L.; Marks, Tobin J.; Mayer, Michael F.; Stoddart, J. Fraser; Findlater, Michael
Abstract: The syntheses of the 2, 9‐dimesityl‐1, 10‐phenanthroline (dmesp ) metal complexes, [Cu(dmesp)(MeCN)]PF6 (1 ), [Cu(dmesp)2 ]PF6 (2 ), Fe(dmesp)Cl2 (3 ), Co(dmesp)Cl2 (4 ), Ni(dmesp)Cl2 (5 ), Zn(dmesp)Cl2 (6 ), Pd(dmesp)MeCl (7 ), Cu(dmesp)Cl (8 ), and Pd(dmesp)2 Cl2 (9 ), in good to high yields are described. These complexes were characterized by 1 H and 13 C NMR spectroscopy, HR–MS (ESI and/or APPI), and elemental analysis (CHN). The solid‐state structures of complexes 1 –8 were determined by single‐crystal X‐ray analysis and their photophysical properties were also characterized. To demonstrate the versatility of this new platform, complexes 3 –5, 8, and 9 were employed in the catalytic oligomerization of ethylene using modified methyl aluminoxane (MMAO) as the cocatalyst, where Co(II) and Ni(II) complexes (4 and 5, respectively) were found to exhibit moderate selectivity for catalytic dimerization of ethylene to butenes over tri‐ or tetramerization. Complex 8 is an effective catalyst of both the commonly encountered "click" reaction and amine arylation chemistries. Complexes 6 and 9 were found to be excellent catalysts for Friedel‐Crafts alkylation and Suzuki‐Miyaura coupling, respectively. Abstract : In this study, 2, 9‐dimesityl‐1, 10‐phenanthroline (dmesp) as a versatile ligand framework is used to synthesize its metal complexes. The complex solid‐state structures were determined using single‐crystal X‐ray analysis, and the photophysical properties were also characterized. It is demonstrated that the Co(II) and Ni(II) complexes are capable of catalyzing the dimerization of ethylene selectively when modified methyl aluminoxane is used as a cocatalyst.